Preparation method of isometric crystal flexible electrolytic copper foil
By using composite additives of aminopyridine, ammonium paratungstate and hydrochloric acid in the electrolytic foil production process, the crystal structure of the copper foil is transformed from columnar crystal to equiaxed crystal, which solves the problem of low fatigue resistance of traditional electrolytic copper foil, and achieves bending resistance comparable to that of the calendered copper foil, and replaces the calendered copper foil to produce flexible copper clad plates or flexible circuit boards.
Patent Information
- Application Number
- CN202411722625.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-18
AI Technical Summary
The fatigue resistance of traditional electrolytic copper foil is lower than that of calendered copper foil, and the calendered copper foil has problems such as high production costs and limited width.
By introducing composite additives of p-aminopyridine, ammonium paratungstate and hydrochloric acid in the electrolytic foil production process, the crystal structure of the copper foil is regulated, and the transformation from columnar crystal to equiaxial crystal is improved, and the mechanical properties of the copper foil are improved.
The tensile strength, elongation and bending resistance of electrolytic copper foil are significantly improved, so that it can replace the rolled copper foil for the preparation of flexible copper clad plates or flexible circuit boards, solving the problems of high production costs and limited width.
Smart Images

Figure HDA0005158427670000011 
Figure HDA0005158427670000012 
Figure HDA0005158427670000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrolytic copper foil, and in particular relates to a method for preparing equiaxed crystal flexible electrolytic copper foil. Background Art
[0002] In recent years, with the rapid development of foldable screen mobile phones, robots, AR, VR and other products, there are increasingly higher requirements for the bending performance of flexible circuit boards (FPC) to meet various special application scenarios of FPC. Flexible copper clad laminate (FCCL) is the processing substrate material of flexible circuit board FPC. It is composed of flexible insulating base film and metal copper foil, and the bending performance of flexible circuit board (FPC) is greatly affected by the bending resistance of copper foil. The flexible copper foil used for flexible circuit boards is divided into rolled copper foil and electrolytic copper foil. The bending resistance of traditional electrolytic copper foil is far inferior to that of rolled copper foil, but rolled copper foil has problems such as long process flow, low yield, high production cost, and limited width. Using electrolytic copper foil to replace rolled copper foil to produce flexible circuit boards has become the current mainstream trend.
[0003] Traditional electrolytic copper foil is prepared by electrodeposition, and its crystal structure is a columnar crystal structure perpendicular to the titanium roller surface, which is quite different from the fibrous structure of rolled copper foil, resulting in the fatigue resistance of electrolytic copper foil being much lower than that of rolled copper foil. The present invention introduces a new composite additive technology in the electrolytic foil production process to regulate the crystal structure of copper foil, and improves the mechanical properties of electrolytic copper foil, such as tensile strength and elongation, by changing the crystallization mode of copper, thereby greatly improving the bending resistance of electrolytic copper foil, and can be used to replace rolled copper foil to prepare flexible circuit boards. Summary of the invention
[0004] The present invention provides a method for preparing an equiaxed flexible electrolytic copper foil, which improves the bending resistance of the electrolytic copper foil. The prepared flexible electrolytic copper foil can be used to replace rolled copper foil to produce flexible copper-clad laminates or flexible circuit boards, thereby solving the problems of high production cost and limited width of the rolled copper foil.
[0005] The present invention provides a method for preparing an equiaxed crystal flexible electrolytic copper foil, comprising the following steps:
[0006] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0007] (2) introducing p-aminopyridine, ammonium paratungstate and hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0008] (3) continuously electroplating the raw foil electrolyte on a cathode roller through a raw foil machine to produce raw foil;
[0009] (4) The bright surface of the raw foil is subjected to a roughening treatment to form a roughened copper nodule structure, thereby obtaining an equiaxed flexible electrolytic copper foil.
[0010] Preferably, the purity of the copper element in step (1) is greater than 99.5%.
[0011] Preferably, the copper ion concentration in the copper sulfate electrolyte in step (1) is 80-100 g / L, and the acid content is 100-140 g / L.
[0012] Preferably, the preheating temperature in step (1) is 50-55°C.
[0013] Preferably, in the raw foil electrolyte in step (2), the chloride ion concentration is 10-30 mg / L, the p-aminopyridine concentration is 5-20 mg / L, and the ammonium paratungstate concentration is 2-10 mg / L.
[0014] Preferably, the electroplating process parameters in step (3) are: the raw foil electrolyte temperature is 50-60°C, the current density is 60-110A / dm 2 .
[0015] Preferably, the crystal structure of the equiaxed flexible electrolytic copper foil obtained in step (4) is an equiaxed crystal structure, and the average grain size is 1.0 to 1.5 μm.
[0016] The present invention also provides an equiaxed crystal flexible electrolytic copper foil obtained by the above preparation method.
[0017] The thickness of the flexible electrolytic copper foil obtained by the present invention is 9-18 μm, the roughness of the treated surface is 1.5-2.5 μm, Ra is 0.20-0.30 μm, the developed surface area ratio Sdr is 15.0-30.0%, and the size of the roughened copper nodules is 0.5-1.5 μm. The roughness of the non-treated surface is 1.0-2.0 μm, Ra is 0.15-0.25 μm, and the developed surface area ratio Sdr is 3.0-8.0%. The room temperature tensile strength is 500-650 MPa, the room temperature elongation is 8-15%, the high temperature tensile strength is 200-250 MPa, and the high temperature elongation is 7-15%.
[0018] The present invention also provides the use of the equiaxed crystal flexible electrolytic copper foil obtained by the above preparation method in a flexible copper-clad laminate or a flexible circuit board.
[0019] The p-aminopyridine in the present invention acts as a leveling agent to reduce the roughness of the raw foil surface; the ammonium paratungstate and p-aminopyridine have a synergistic effect, which can regulate the growth of raw foil grains and transform the grains from columnar crystals to equiaxed crystals. Hydrochloric acid mainly provides chloride ions, which act as "chlorine bridges" in electrolytic copper foil, connecting additive molecules with copper ions and accelerating the deposition of copper ions into copper atoms.
[0020] Beneficial Effects
[0021] The present invention uses a composite additive of p-aminopyridine, ammonium paratungstate and hydrochloric acid in the electrolytic foil process to achieve the transformation of the copper foil crystal structure from columnar crystals to fine equiaxed crystals. On the one hand, the roughness of the raw foil surface is reduced, which is conducive to improving the etching performance of the copper foil and is suitable for the preparation of FPC fine circuits; on the other hand, the tensile strength and elongation of the copper foil are improved through the fine crystal strengthening effect, so that its bending resistance is greatly improved. The flexible electrolytic copper foil prepared by the present invention can be used to replace the rolled copper foil to produce flexible copper clad laminates or flexible circuit boards, solving the problems of high production cost and limited width of the rolled copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 EBSD of the cross section of 12 μm copper foil of Comparative Example 1;
[0023] Figure 2 This is the EBSD of the cross section of the 12 μm copper foil in Example 1;
[0024] Figure 3 This is the SEM morphology of the non-treated surface of the 12 μm copper foil in Example 1;
[0025] Figure 4 This is the SEM morphology of the processed surface of the 12μm copper foil in Example 1. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0027] Comparative Example 1
[0028] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0029] (2) introducing hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0030] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0031] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0032] The copper ion concentration of the raw foil electrolyte is 90g / L, the acid content is 120g / L, the chloride ion concentration is 20mg / L, and there is no additive. The temperature of the raw foil electrolyte is 54℃, and the current density is 80A / dm 2 .
[0033] Under the above process conditions, the physical properties of the 12μm finished copper foil are as follows:
[0034] The roughness of the treated surface: Rz is 2.01μm, Ra is 0.26μm, the interface expansion area ratio Sdr is 20.80%, and the average size of the roughened copper nodules is 1.02μm. The roughness of the non-treated surface: Rz is 2.86μm, Ra is 0.34μm, and the interface expansion area ratio Sdr is 17.08%. The tensile strength at room temperature is 414MPa, and the elongation at room temperature is 7.8%; the tensile strength at high temperature (180℃, 5min) is 175MPa, and the elongation at high temperature is 11.4%. Figure 1 As shown, the crystal structure of the copper foil cross section is a mixed structure of columnar crystals and equiaxed crystals, with an average grain size of 2.1 μm. The crystal structure is unstable and is prone to recrystallization at high temperatures.
[0035] Comparative Example 2
[0036] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0037] (2) introducing hydrochloric acid and p-aminopyridine into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0038] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0039] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0040] In the raw foil electrolyte, the copper ion concentration is 90g / L, the acid content is 120g / L, the chloride ion concentration is 20mg / L, and the aminopyridine concentration is 20mg / L. The temperature of the raw foil electrolyte is 54℃, and the current density is 80A / dm 2 .
[0041] Under the above process conditions, the physical properties of the 12μm finished copper foil are as follows:
[0042] The roughness of the treated surface: Rz is 2.11μm, Ra is 0.26μm, the interface expansion area ratio Sdr is 21.60%, and the average size of the roughened copper nodules is 1.04μm. The roughness of the non-treated surface: Rz is 2.79μm, Ra is 0.33μm, and the interface expansion area ratio Sdr is 16.98%. The tensile strength at room temperature is 419MPa, and the elongation at room temperature is 8.3%; the high-temperature tensile strength (180℃, 5min) is 195MPa, and the high-temperature elongation is 8.5%. The crystal structure of the copper foil cross section is a mixed structure of columnar crystals and equiaxed crystals, with an average grain size of 2.2μm. The crystal structure is unstable and is prone to recrystallization at high temperatures.
[0043] Comparative Example 3
[0044] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0045] (2) introducing hydrochloric acid and p-aminopyridine into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0046] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0047] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0048] In the raw foil electrolyte, the copper ion concentration is 90g / L, the acid content is 120g / L, the chloride ion concentration is 20mg / L, and the ammonium paratungstate concentration is 10mg / L. The temperature of the raw foil electrolyte is 54℃, and the current density is 80A / dm 2 .
[0049] Under the above process conditions, the physical properties of the 12μm finished copper foil are as follows:
[0050] The roughness of the treated surface: Rz is 2.05μm, Ra is 0.25μm, the interface expansion area ratio Sdr is 20.10%, and the average size of the roughened copper nodules is 1.02μm. The roughness of the non-treated surface: Rz is 3.19μm, Ra is 0.36μm, and the interface expansion area ratio Sdr is 19.98%. The tensile strength at room temperature is 389MPa, and the elongation at room temperature is 10.3%; the tensile strength at high temperature (180℃, 5min) is 201MPa, and the elongation at high temperature is 7.2%. The crystal structure of the copper foil cross section is a mixed structure of columnar crystals and equiaxed crystals, with an average grain size of 2.6μm. The crystal structure is unstable and is prone to recrystallization at high temperatures.
[0051] Comparative Example 4
[0052] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0053] (2) introducing hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0054] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0055] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0056] The copper ion concentration of the raw foil electrolyte is 90g / L, the acid content is 120g / L, the chloride ion concentration is 20mg / L, and there is no additive. The temperature of the raw foil electrolyte is 54℃, and the current density is 80A / dm 2 .
[0057] Under the above process conditions, the physical properties of the 9μm finished copper foil are as follows:
[0058] The roughness of the treated surface: Rz is 1.62μm, Ra is 0.24μm, the interface expansion area ratio Sdr is 16.82%, and the average size of the roughened copper nodules is 1.06μm. The roughness of the non-treated surface: Rz is 2.26μm, Ra is 0.30μm, and the interface expansion area ratio Sdr is 15.08%. The tensile strength at room temperature is 423MPa, and the elongation at room temperature is 5.6%; the high-temperature tensile strength (180℃, 5min) is 178MPa, and the high-temperature elongation is 9.3%. The crystal structure of the copper foil cross section is a mixed structure of columnar crystals and equiaxed crystals, with an average grain size of 1.8μm. The crystal structure is unstable and is prone to recrystallization at high temperatures.
[0059] Comparative Example 5
[0060] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0061] (2) introducing hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0062] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0063] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0064] The copper ion concentration of the raw foil electrolyte is 90g / L, the acid content is 120g / L, the chloride ion concentration is 20mg / L, and there is no additive. The temperature of the raw foil electrolyte is 54℃, and the current density is 80A / dm 2 .
[0065] Under the above process conditions, the physical properties of the 18μm finished copper foil are as follows:
[0066] The roughness of the treated surface: Rz is 2.51μm, Ra is 0.29μm, the interface expansion area ratio Sdr is 31.20%, and the average size of the roughened copper nodules is 1.25μm. The roughness of the non-treated surface: Rz is 3.88μm, Ra is 0.40μm, and the interface expansion area ratio Sdr is 25.41%. The tensile strength at room temperature is 406MPa, and the elongation at room temperature is 10.2%; the high-temperature tensile strength (180℃, 5min) is 181MPa, and the high-temperature elongation is 15.7%. The crystal structure of the copper foil cross section is a mixed structure of columnar crystals and equiaxed crystals, with an average grain size of 2.7μm. The crystal structure is unstable and is prone to recrystallization at high temperatures.
[0067] Example 1
[0068] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0069] (2) introducing p-aminopyridine, ammonium paratungstate and hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0070] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0071] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0072] In the raw foil electrolyte, the copper ion concentration is 90g / L, the acid content is 120g / L, the chloride ion concentration is 20mg / L, the p-aminopyridine concentration is 20mg / L, and the ammonium paratungstate concentration is 10mg / L. The temperature of the raw foil electrolyte is 54℃, and the current density is 80A / dm 2 .
[0073] Under the above process conditions, the physical properties of the 12μm finished copper foil are as follows:
[0074] The roughness of the treated surface: Rz is 2.01μm, Ra is 0.26μm, the interface expansion area ratio Sdr is 20.80%, and the average size of the roughened copper nodules is 0.82μm. The roughness of the non-treated surface: Rz is 1.54μm, Ra is 0.20μm, and the interface expansion area ratio Sdr is 4.75%. The tensile strength at room temperature is 597MPa, and the elongation at room temperature is 9.8%; the tensile strength at high temperature (180℃, 5min) is 249MPa, and the elongation at high temperature is 10.6%. Figure 2 As shown, the crystal structure of the copper foil cross section is a fine equiaxed crystal structure with an average grain size of 1.1 μm. The crystal structure is stable and no recrystallization occurs at high temperatures. Figure 3 , 4 The electron microscope morphologies of the untreated and treated surfaces of the copper foil are shown respectively. The untreated surface has a flat peak shape and low roughness. During repeated bending of the copper foil, the surface cracks are not easy to expand and the flexural properties are excellent. The copper nodule particles on the treated surface are smaller and evenly distributed, and have higher peel strength after being pressed with PI.
[0075] Example 2
[0076] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0077] (2) introducing p-aminopyridine, ammonium paratungstate and hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0078] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0079] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0080] In the raw foil electrolyte, the copper ion concentration is 80g / L, the acid content is 100g / L, the chloride ion concentration is 10mg / L, the p-aminopyridine concentration is 5.0mg / L, and the ammonium paratungstate concentration is 2.0mg / L. The temperature of the raw foil electrolyte is 60℃, and the current density is 70A / dm 2 .
[0081] Under the above process conditions, the physical properties of the 12μm finished copper foil are as follows:
[0082] The roughness of the treated surface: Rz is 2.20μm, Ra is 0.27μm, the interface expansion area ratio Sdr is 25.80%, and the average size of the roughened copper nodules is 0.91μm. The roughness of the non-treated surface: Rz is 1.96μm, Ra is 0.23μm, and the interface expansion area ratio Sdr is 7.82%. The tensile strength at room temperature is 505MPa, and the elongation at room temperature is 13.5%; the tensile strength at high temperature (180℃, 5min) is 209MPa, and the elongation at high temperature is 14.6%. The crystal structure of the copper foil cross section is a fine equiaxed crystal structure with an average grain size of 1.4μm. The crystal structure is stable and no recrystallization occurs at high temperatures.
[0083] Example 3
[0084] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0085] (2) introducing p-aminopyridine, ammonium paratungstate and hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0086] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0087] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0088] In the raw foil electrolyte, the copper ion concentration is 90g / L, the acid content is 140g / L, the chloride ion concentration is 30mg / L, the p-aminopyridine concentration is 10.0mg / L, and the ammonium paratungstate concentration is 5.0mg / L. The temperature of the raw foil electrolyte is 50℃, and the current density is 110A / dm 2 .
[0089] Under the above process conditions, the physical properties of the 12μm finished copper foil are as follows:
[0090] The roughness of the treated surface: the contact type Rz is 1.89μm, Ra is 0.25μm, the interface expansion area ratio Sdr is 17.86%, and the average size of the roughened copper nodules is 0.80μm. The roughness of the non-treated surface: Rz is 1.76μm, Ra is 0.21μm, and the interface expansion area ratio Sdr is 6.61%. The tensile strength at room temperature is 553MPa, and the elongation at room temperature is 12.6%; the tensile strength at high temperature (180℃, 5min) is 239MPa, and the elongation at high temperature is 13.4%. The crystal structure of the copper foil cross section is a fine equiaxed crystal structure with an average grain size of 1.2μm. The crystal structure is stable and no recrystallization occurs at high temperatures.
[0091] Example 4
[0092] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0093] (2) introducing p-aminopyridine, ammonium paratungstate and hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0094] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0095] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0096] In the raw foil electrolyte, the copper ion concentration is 90g / L, the acid content is 120g / L, the chloride ion concentration is 20mg / L, the p-aminopyridine concentration is 20mg / L, and the ammonium paratungstate concentration is 10mg / L. The temperature of the raw foil electrolyte is 54℃, and the current density is 80A / dm 2 .
[0097] Under the above process conditions, the physical properties of the 9μm finished copper foil are as follows:
[0098] The roughness of the treated surface: Rz is 1.56μm, Ra is 0.23μm, the interface expansion area ratio Sdr is 15.49%, and the average size of the roughened copper nodules is 0.72μm. The roughness of the non-treated surface: Rz is 1.14μm, Ra is 0.15μm, and the interface expansion area ratio Sdr is 3.25%. The tensile strength at room temperature is 630MPa, and the elongation at room temperature is 7.3%; the tensile strength at high temperature (180℃, 5min) is 255MPa, and the elongation at high temperature is 8.6%. The crystal structure of the copper foil cross section is a fine equiaxed crystal structure with an average grain size of 1.0μm. The crystal structure is stable and no recrystallization occurs at high temperatures.
[0099] Example 5
[0100] (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification;
[0101] (2) introducing p-aminopyridine, ammonium paratungstate and hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte;
[0102] (3) the raw foil electrolyte is continuously electroplated on a cathode roller through a raw foil machine to produce raw foil, wherein the electrolytic cathode of the raw foil machine is a seamless drum-type titanium roller, and the electrolytic anode is a DSA-coated titanium anode plate;
[0103] (4) Roughening the surface of the raw copper foil to prepare the finished copper foil.
[0104] In the raw foil electrolyte, the copper ion concentration is 90g / L, the acid content is 120g / L, the chloride ion concentration is 20mg / L, the p-aminopyridine concentration is 20mg / L, and the ammonium paratungstate concentration is 10mg / L. The temperature of the raw foil electrolyte is 54℃, and the current density is 80A / dm 2 .
[0105] Under the above process conditions, the physical properties of the 18μm finished copper foil are as follows:
[0106] The roughness of the treated surface: Rz is 2.46μm, Ra is 0.28μm, the interface expansion area ratio Sdr is 29.78%, and the average size of the roughened copper nodules is 1.22μm. The roughness of the non-treated surface: Rz is 2.48μm, Ra is 0.30μm, and the interface expansion area ratio Sdr is 9.67%. The tensile strength at room temperature is 582MPa, and the elongation at room temperature is 14.8%; the tensile strength at high temperature (180℃, 5min) is 238MPa, and the elongation at high temperature is 15.3%. The crystal structure of the copper foil cross section is a fine equiaxed crystal structure with an average grain size of 1.5μm. The crystal structure is stable and no recrystallization occurs at high temperatures.
[0107] It can be seen from the embodiments and comparative examples that by introducing the composite additive of p-aminopyridine, ammonium paratungstate and hydrochloric acid in the electrolytic foil production process, the roughness of the non-treated surface can be effectively reduced, and the crystal structure of the copper foil is transformed from columnar crystals to fine equiaxed crystals. Such fine equiaxed grains make the copper foil have higher tensile strength and elongation, and the crystal structure is very stable. In the process of flexible copper clad laminate, annealing recrystallization will not occur due to high temperature, which will affect the dimensional stability and etching properties of the sheet material, and is very suitable for fine-line flexible circuit boards.
Claims
1. A method for preparing an equiaxed flexible electrolytic copper foil, comprising the following steps: (1) adding copper to a copper dissolving tank containing sulfuric acid to dissolve into a copper sulfate electrolyte, and then preheating after multi-stage filtration and purification; (2) introducing p-aminopyridine, ammonium paratungstate and hydrochloric acid into the copper sulfate electrolyte to obtain a raw foil electrolyte; (3) continuously electroplating the raw foil electrolyte on a cathode roller through a raw foil machine to produce raw foil; (4) The bright surface of the raw foil is subjected to a roughening treatment to form a roughened copper nodule structure, thereby obtaining an equiaxed flexible electrolytic copper foil.
2. The preparation method according to claim 1, characterized in that: The purity of the copper element in step (1) is greater than 99.5%.
3. The preparation method according to claim 1, characterized in that: The copper ion concentration in the copper sulfate electrolyte in the step (1) is 80-100 g / L, and the acid content is 100-140 g / L.
4. The preparation method according to claim 1, characterized in that: In the step (2), the concentration of chloride ions in the raw foil electrolyte is 10-30 mg / L, the concentration of p-aminopyridine is 5-20 mg / L, and the concentration of ammonium paratungstate is 2-10 mg / L.
5. The preparation method according to claim 1, characterized in that: The electroplating process parameters in step (3) are: the raw foil electrolyte temperature is 50-60°C, the current density is 60-110A / dm 2 .
6. The preparation method according to claim 1, characterized in that: The crystal structure of the equiaxed flexible electrolytic copper foil obtained in the step (4) is an equiaxed crystal structure, and the average grain size is 1.0 to 1.5 μm.
7. An equiaxed flexible electrolytic copper foil obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the equiaxed flexible electrolytic copper foil obtained by the preparation method according to any one of claims 1 to 6 in a flexible copper-clad laminate or a flexible circuit board.